2012
DOI: 10.1002/adfm.201202174
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Fiber Based Stretchable Conductor

Abstract: Carbon nanotube (CNT) based continuous fiber, a CNT assembly that could potentially retain the superb properties of individual CNTs on a macroscopic scale, belongs to a fascinating new class of electronic materials with potential applications in electronics, sensing, and conducting wires. Here, the fabrication of CNT fiber based stretchable conductors by a simple prestraining‐then‐buckling approach is reported. To enhance the interfacial bonding between the fibers and the poly(dimethylsiloxane) (PDMS) substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 28 publications
0
69
0
Order By: Relevance
“…[9][10][11][12][13][14] It remains a great challenge to develop highly elastic wire-shaped electronics because most of the existing wires are either stretchable, but nonconductive (e.g., elastic polymer fibers), or vice versa (e.g., metal wires). A few studies on stretchable conductive wires have been reported, [15,16] whereas the development of stretchable wire-shaped electronics has been much less discussed in the literature. However, if such electronics (e.g., supercapacitors) are realized, they could be very useful as power sources for various miniaturized electronic devices, ranging from microrobots, through wearable electronic textiles, to integrated energy conversion and storage systems.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] It remains a great challenge to develop highly elastic wire-shaped electronics because most of the existing wires are either stretchable, but nonconductive (e.g., elastic polymer fibers), or vice versa (e.g., metal wires). A few studies on stretchable conductive wires have been reported, [15,16] whereas the development of stretchable wire-shaped electronics has been much less discussed in the literature. However, if such electronics (e.g., supercapacitors) are realized, they could be very useful as power sources for various miniaturized electronic devices, ranging from microrobots, through wearable electronic textiles, to integrated energy conversion and storage systems.…”
mentioning
confidence: 99%
“…Meanwhile, the specific capacitance of the stretchable supercapacitors with or without applied strain does not alter up to 1000 charge-discharge cycles, which concludes an excellent electrochemical stability [28]. To further enhance the stretchability while retaining high electric conductivity, the architectures of this wave structural configuration are carefully tailored by finely designing the CNTs with various morphologies and spatial distributions, such as CNT fibers [32], CNT ribbons [33], aligned CNTs [34], and hierarchically reticulated CNTs [35]. The similar buckling strategy can also be applied to other energy storage devices.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…It turned out that massive buckling took place in the fractured CNT fiber segments. Taking advantage of the "hinge-like" structure developed in the buckled fiber, Zu et al [16] developed a stretchable conductor, which showed very little variation in electric resistance under stretchingthen-releasing cycles with a maximum strain of 40%. Expanding the capability of CNT fiber based stretchability, Xu et al [17] studied a stretchable supercapacitor consisting of two undulating CNT fibers.…”
Section: Introductionmentioning
confidence: 99%